Effect of ethyl cellulose on thermal resistivity of thixotropic ZnO nano-particle paste for thermal interface material in light emitting diode application. (February 2017) - Wen, Mah Jian; Subramani, Shanmugan; Devarajan, Mutharasu; Sulaiman, Fauziah
Abstract: A large amount of heat trapped inside Light Emitting Diode (LED) is the consequence of large thermal resistance between the heat source and the heat sink. Zinc oxide (ZnO) thick film was screen-printed from thixotropic paste that consisted of binder, filler and solvent to act as thermal interface material. Structural, surface morphology, vibrational and thermal properties of the samples were studied by means of Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Measurement (AFM), Fourier Transform Infrared Spectroscopy (FTIR) and Thermal Transient Tester (T3ster). XRD analysis revealed that the formation of hexagonal wurtzite ZnO powder, which is free of hydroxide. FESEM results indicated that 50 wt% of filler loading in the thick film had created longer thermal transportation chain. The surface roughness of thick film displays variation in the range of from 64.8 to 218 nm. The presence of ZnO and binder were confirmed by FTIR spectrum at 518 cm −1 and 668 cm −1 to 2974 cm −1, respectively. Thermal characterization reveals a drop in film's resistivity with the higher content of filler loading of 50 wt% and 55 wt%. The lowest rise in junction temperature of tested LED is reported to be 14.7 °C of 50 wt% of filler loading.